Rancangan Aplikasi Presensi Karyawan CV. Pramana Mukti Jaya menggunakan Metode Extreme programming (XP) Berbasis Web dengan Integrasi Teknologi Leaflet.JS - Nosiyanto, Bayu; Faizah, NM; Nurcahyo, Widyat (Yayasan Kawanad, 2024)
Employee attendance management is an integral part of company operations. This study aims to develop a web-based employee attendance application at CV Pramana Mukti Jaya, integrated with Leaflet.js technology. This application enables employees to report their attendance efficiently and accurately through a responsive web interface. The development method used is Extreme Programming (XP) to ensure rapid iterations and active stakeholder participation. During the analysis phase, both functional and non-functional requirements of the application were identified. The application allows CV Pramana Mukti Jaya employees to record attendance by inputting time and location information directly through a web form. With the integration of Leaflet.js technology, the application provides an interactive map that facilitates employees in selecting accurate attendance locations. The application testing was conducted to verify the accuracy and ease of use of the Leaflet.js map interactions. The result of this research is an effective web-based employee attendance application at CV Pramana Mukti Jaya. The integration of Leaflet.js technology provides a significant visual dimension in employee attendance reporting. This application is expected to help the company manage employee attendance more efficiently and accurately while introducing the benefits of implementing Leaflet.js technology in web-based applications.